Spatial analysis of solar panel imports in the state of Minas Gerais (2010-2024) - Nunes, Raissa Oliveira; Oliveira, Gustavo Henrique Gomes de; Leite, Marcos Esdras (Geografares, 2026)
Solar energy is one of the renewable energy sources in which the country has great potential for its dissemination throughout the national territory. Therefore, one of the aspects contributing to this process is solar panels, whose characteristics, linked to high costs and accessibility, are one of the determining factors for their development. Thus, this article aims to understand the dynamics of solar panel imports in the state of Minas Gerais from 2010 to 2024, adding geoprocessing and decision-making techniques. It concludes that the increase was significant, since 78.57% of the years analyzed showed average annual growth rates of 200,28%.
Keywords: solar panels; imports; ports; Minas Gerais